Dolžniško financiranje in tanka kapitalizacija - Hauptman, Lidija (Management, 2014)
Since each form of financing provides a different level of security and risk, companies are often faced with a dilemma, which equity to debt ratio to choose in financial structure. In order to avoid overexploitation of certain types of debt financing, tax legislation defines a thin capitalization rule. In this paper we present, how the relationship between equity and debt financing has changed in the period 1997--2012 and how the thin capitalization rules affected this relationship in the selected parent companies in Slovenia. The analysis reveals that the proportion of debt financing increased before and after the introduction of thin capitalization rules throughout the period.
Keywords: financiranje; podjetja; poslovne finanace; računovodski izkazi; zadolženost